Skateboarder and scooter-rider perceptions of the urban environment: a qualitative analysis of user-generated content. Issue 10 (26th November 2021) - Platt, Lorne; Rybarczyk, Greg
ABSTRACT: Personal Mobility Devices such as skateboards and scooters are increasingly considered a form of active transportation in dense urban environments. Understanding the experience of users is paramount, especially for cities intent on implementing efficient policies that promote sustainable futures. To meet this need, the research examined the dynamic relationships between the built environment and PMD users in Los Angeles, California. The data used in this study were derived from Instagram posts, and we implemented a participatory digital-photo/diary methodology to investigate how travelers responded to urban features. Our findings suggest that many riders encountered rough surfaces and difficult transitions. Additionally, several built environment types, including well-maintained surfaces, were noted for the relative ease with which they could be ridden. The overall findings tell us that cities need to acknowledge this evidence and apply this toward long-term efforts set on facilitating these active mobilities in an urban setting.